Standardization and improvement of influenza surveillance: memorandum from a WHO/GEIG meeting. (World Health Organization, 1992)
The main objectives of influenza surveillance are early detection of influenza outbreaks and identification of the causative agent, collection and analysis of influenza morbidity and mortality data, and collection of influenza virus isolates and analysis of their antigenic characteristics. The true morbidity and mortality from influenza are difficult to estimate in most countries on the basis of only reports of influenza-like illnesses. Analysis and comparisons of the impact of influenza in different countries are also difficult because surveillance systems and methods vary from one country to another. This Memorandum describes generally applicable systems that could improve influenza surveillance.